THE EFFECT OF ECONOMIC GROWTH, REGIONAL EXPENDITURES, AND POVERTY LEVELS IN EAST KALIMANTAN PROVINCE - Dzulqornain, Rifqi; Iriani.S.E.Ak, M.E, Dr.Dra.Ec. Ririt (JEA17: Jurnal Ekonomi Akuntansi, 2022)
The Human Development Index (HDI) is a composite in measuring human development achievements based on the basic components of quality of life. The Human Development Index (HDI) is a single combined/mixed indicator that cannot measure all of the dimensions of human development, but measures three main dimensions of human development, namely longevity and health, knowledge and skills and access to the resources needed to achieve a decent life. In this study, the population used was the Province of East Kalimantan in a span of 12 years from 2010 -2021. This study aims to determine the effect of Economic Growth, Regional Expenditures, and Poverty Levels on the Human Development Index (IPM) in East Kalimantan Province for the 2010-2021 period. The data analysis method in this study is panel data regression using SPSS version 24 software. The results of the study show simultaneously that the independent variables consisting of Economic Growth, Regional Expenditures, Poverty Levels have a significant influence on HDI. While the partial test of Economic Growth and Regional Expenditures has no effect on HDI. And the Poverty Level has a negative effect on HDI